Molecular Analysis of Pediatric Oligodendrogliomas Highlights Genetic Differences with Adult Counterparts and Other Pediatric Gliomas. (14th August 2015) - Nauen, David; Haley, Lisa; Lin, Ming‐Tseh; Perry, Arie; Giannini, Caterina; Burger, Peter C.; Rodriguez, Fausto J.
Abstract: Oligodendroglioma represents a distinctive neoplasm in adults but similar neoplasms occur rarely in children. We studied 20 cases of pediatric oligodendroglioma by SNP array (median age 9 years, range 1–19; 15 grade II and 5 grade III). Cytogenetic abnormalities were present in 8 (53%) grade II and all five anaplastic oligodendrogliomas. Most changes were in the form of deletion and copy neutral loss of heterozygosity (LOH). The most common abnormality was 1p deletion (n = 5). Whole arm 1p19q co‐deletion was present in three cases from adolescent patients and 9p loss in 3, including one low‐grade oligodendroglioma with CDKN2A homozygous deletion. Common losses were largely limited to the anaplastic subset (n = 5) and included 3q29 (n = 3), 11p (n = 3), 17q (n = 3), 4q (n = 2), 6p (n = 2), 13q (n = 2), 14q (n = 2), 17p (n = 2) and whole Ch 18 loss (n = 2). Gains were non‐recurrent except for whole Ch 7 (n = 2) and gain on 12q (n = 2) including the MDM2 locus. Possible germ line LOH (or uniparental disomy) was present in seven cases (35%), with one focal abnormality (22q13.1‐13.2) in two. BRAF‐KIAA1549 fusions and BRAF p.V600E mutations were absent (n = 13 and 8). In summary, cytogenetic alterations in pediatric oligodendrogliomas are characterized mostly by genomic losses, particularly in anaplastic tumors.